SYNTHESIS AND PRELIMINARY PHARMACOLOGICAL EVALUATION OF NEW NAPROXEN ANALOGUES HAVING 1, 2, 4-TRIAZOLE-3-THIOL - Mahdi, Monther F.; Naser, Noor H.; Hammud, Nethal H. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
<!–[if gte mso 9]> <![endif]–> Objective: The objective of this search was to synthesize a new naproxen analogues having a 1,2,4-triazole-3-thiol heterocyclic ring, and preliminary pharmacological assessment of the anti-inflammatory activity of the synthesized compounds. Methods: The synthesis of naproxen analogues that having 1,2,4-triazole-3-thiol heterocyclic ring occur through esterification of naproxen, and then its reaction with hydrazine hydrate, and carbon disulfide, finally different aromatic aldehydes reacted with triazole derivatives of naproxen containing amino group to produce schiff bases. Results: In vivo acute anti-inflammatory activity of the synthesize compounds (Va-Vd) was evaluated in rats using egg-white induced edema model of inflammation in a dose equivalent to (50 mg/kg) of naproxen. All tested compounds were produced a significant reduction in paw edema with respect to the effect of propylene glycol 50% v/v (control group). Compound Vd produced superior anti-inflammatory activity compared to naproxen. Conclusion: The results obtained in this work give evidence about the valid synthesis of 1,2,4 triazole-3-thiol derivatives of naproxen, which reacted with different aldehydes to yield several schiff bases. The incorporation of benzaldehyde possess para-electron donating group (para-hydroxyl benzaldehyde) will increase the anti-inflammatory activity of naproxen. <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>